Liver transplantation for fulminant hepatic failure in yellow phosphorus poisoning (Indian Journal of Case Reports, 2022)
Yellow phosphorus (YP) containing rodenticides is a readily available poison that may be accidentally or deliberately ingested, leading to symptoms ranging from simple gastrointestinal symptoms to fulminant hepatic failure, depending on the amount ingested. As there is no specific antidote, the treatment requires early gastric lavage and institution of supportive measures such as acetyl cysteine infusion and Vitamin K. Progression to fulminant hepatic failure is characterized by rapid deterioration of liver function tests, worsening coagulopathy, and sensorium. The only definitive treatment at this stage is a liver transplant and therapeutic plasma exchange (TPE) can serve as a bridge therapy until a compatible liver donor is found. We present a case of YP-containing rodenticide poisoning, in which the patient progressed to fulminant hepatic failure despite aggressive supportive therapy and was successfully managed with TPE until liver transplantation.